Waste Management Towards a Clean City Case Study of the Kupang City Environmental and Sanitation Service - Marlen Yollanda KARIMOY; Maria Magadalena LINO; Hendrik TODA (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to examine waste management in Kupang City through the lens of George R. Terry’s POAC (Planning, Organizing, Actuating, Controlling) management theory. Waste problems in Kupang are increasingly complex due to rapid population growth, limited infrastructure, and insufficient public awareness. Effective waste management requires synergy among the local government, the community, and the private sector. Based on the study, the Kupang City Department of Environment and Hygiene (DLHK) has implemented the POAC functions to some extent. Planning and organizing have been conducted through regional policies and work programs, while actuating is reflected in the daily operations of waste collection and public education efforts. However, challenges remain—such as a lack of community participation, limited budget and waste-handling equipment, and weak supervision mechanisms. Despite these obstacles, the study found several supporting factors: existing mayoral regulations (Perwali), backing from security forces in law enforcement, and community-driven initiatives in independent waste management. To address current gaps, the study recommends strengthening institutional capacity, increasing funding allocation, improving public awareness, and fostering better coordination across stakeholders. In the long term, a collaborative and participatory approach is essential to achieve a clean, healthy, and sustainable urban environment in Kupang City.